Pengaruh Job Insecurity terhadap Turnover Intention melalui Stres Kerja sebagai Variabel Intervening pada Karyawan PT. Sumber Alfaria Trijaya Tbk. (Alfamart) - Zailani Hamzah; Ika Yuliana (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
High employee turnover has become a critical issue in the retail industry, particularly due to increasing employment uncertainty and work-related pressure. Job insecurity experienced by employees may lead to psychological stress, which in turn encourages the intention to leave the organization. This study aims to examine the effect of job insecurity on turnover intention, with work stress acting as an intervening variable among employees of PT. Sumber Alfaria Trijaya Tbk. (Alfamart). A quantitative approach was employed using a survey method. Data were collected from 100 employees selected through purposive sampling, consisting of permanent and contract workers with a minimum of one year of service. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The results indicate that job insecurity has a positive and significant effect on turnover intention. In addition, job insecurity significantly increases work stress, which also has a significant positive effect on turnover intention. The mediation analysis confirms that work stress partially mediates the relationship between job insecurity and turnover intention. These findings suggest that employment uncertainty contributes to psychological strain, which strengthens employees’ intentions to leave the organization. The study highlights the importance of managing job security perceptions and work stress to reduce turnover intention in the retail sector.